Visual forms and color palette of Francesca Romana's holiness at Tor de' Specchi in Rome - Daniele, Elisa Antonietta,Gallicchio, Pamela (Ikon;Rijeka, 2021;Band 14 (2021), Seite 177-188, 2021)
This article explores the two fresco cycles devoted to Saint Francesca Romana (Francesca Bussa de’ Leoni 1384-1440) in the monastery of Tor de’ Specchi in Rome, founded in 1433. The two cycles, created by different painters twenty years apart, are situated in two adjoining spaces of the monastery. The first, attributed to Antoniazzo Romano, was frescoed in 1468 in a space used for prayer and mass (the Oratorio) and represents her charitable actions, miracles, and celestial visions. The second cycle dated to 1485, in terra verde technique, is situated in the ancient refectory and depicts Francesca Romana’s encounter with demonic creatures. Intriguingly, although Francesca was not canonized until 1608, she is presented as a saint in both cycles. We analyze the two parietal decorations in relation to their sources, the Tractato delli visioni di santa Francesca Romana and Tractato delle bactaglie. These two texts were written in Roman vulgar by Francesca’s confessor, Giovanni Mattiotti, in 1447 to record her divine visions and battles with evil. By focusing on selected scenes from both the cycles, we ascertain how closely the images adhere to Mattiotti’s written accounts or, instead, the autonomy of the images. The aim is to grasp how images and words work together in dialogue and how, thanks to this interaction, the different polarities inherent to holiness can be rendered visual. Indeed, whereas the colorful scenes show aspects of holiness linked to a vivifying dimension - Francesca is welcomed into the heavenly realm in the presence of Christ and the Virgin - the terra verde images depict a noxious dimension characterized by light deprivation, indoor spaces, and opposition to the Devil’s torments. Ultimately, by investigating visual forms, material aspects, and narrative strategies, we unearth how Francesca’s sainthood status has been translated and codified.
Keywords: Mattiotti; Giovanni; Franziska; Antoniazzo; Freskomalerei; Heiligenbild; Heiligenvita; Wandmalerei